The Study of Platelet Parameters- Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) in Type 2 Diabetes Mellitus - Joshi, Advait Anirudha; Jaison, Janice (Annals of Pathology and Laboratory Medicine, 2019)
Background: Diabetes Mellitus is a global public health problem with morbidity due to complications caused by macrovascular and microvascular disease. Platelet parameters like Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) are related to platelet size, enzymatic activity and prothrombotic potential. These parameters can be obtained from routine hemogram reports of automated hematology analyzers at a relatively low cost. Fasting blood glucose, postprandial blood glucose, and hemoglobin A1C (HbA1c) are widely used to monitor glycaemic control in patients with DM. The aim of this study is to study Platelet parameters- Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) in type 2 diabetes and its predictive role in diabetic angiopathies. Methods: The present study was a Case control study carried for a period of 2 months. Statistical analysis was done with appropriate tests. Result: MPV values were lower in cases than controls. In controls, MPV shows a negative correlation with fasting blood sugar while in cases it shows a positive correlation with fasting blood sugar. MPV showed no association with HbA1c. PDW was high in cases than controls. In controls, negative correlation between PDW and FBS was observed, while in cases, a positive correlation was observed. A strong association between PDW and HbA1c was noted. At a cut off of 9.5 fL, MPV had a sensitivity of 78.33%, specificity of 70% and a positive predictive value of 72.30%. At a cut off of 15fL, PDW showed a sensitivity of 81.66%, specificity of 91.66% and a positive predictive value of 90.74%. Conclusion: The present study shows strong association between PDW and HbA1c and so it can be used as an indicator of impending vascular events. Of all the platelet parameters obtained by haematology cell counters, Platelet count is only widely used as investigative tool. Platelet indices can be used as simple and cost effective bio markers for predicting diabetic vascular complications.